(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2010)
A total of four compounds namely betulin (1), erythrodiol (2), lupeol (3), and stigmasterol were isolated from the leaf extract of Ixora arborea for the first time. The structures of the isolated compounds were established by extensive spectroscopic studies. In our preliminary screening, the petroleum ether, carbon tetrachloride, dichloromethane and aqueous soluble fractions of the methanol extract were subjected to antioxidant, antimicrobial and brine shrimp lethality bioassays. All of the fractions showed significant antioxidant activity along with the total phenolic content, of which the methanolic extract of leaves (MEL) showed the highest free radical scavenging activity with IC50 value 33.0 μg/ml. In the brine shrimp lethality bioassay, among all the extractives the petroleum ether soluble fraction (PESF) demonstrated significant cytotoxicity with LC50 value of 0.622 μg/ml. However, in case of antimicrobial screening, only the methanolic crude extract showed mild growth inhibitory activity against the tested microorganisms. Key words: Ixora arborea; betulin; erythrodiol; lupeol; stigmasterol; antioxidant; cytotoxicity; antimicrobial DOI: 10.3329/dujps.v8i2.6031 Dhaka Univ. J. Pharm. Sci. 8(2): 161-166, 2009 (December)